DINAMIKA PERTIMBANGAN HAKIM DALAM PENETAPAN DISPENSASI NIKAH DI PENGADILAN AGAMA MAKASSAR: (Perspektif Maqashid As-Syariah Imam Al-Syatibi) - Nur Ahmad; Saleh Ridwan (ISTIQRA: Jurnal Hasil Penelitian, 2024)
This study aims to investigate the dynamics of judges' considerations in determining marriage dispensation at the Makassar Religious Court from the perspective of Maqashid As-Syariah according to Imam Al-Syatibi, focusing on the principles of dharuriyyat, tahsiniyat, and hajjiyat. The research method used is descriptive analytical with a juridical, normative, and sharia approach, and combines field research and library research. Data were collected through interviews with judges and documentation of related decisions. The data analysis technique used is qualitative analysis, which involves grouping and interpreting data according to the principles of Maqashid Syariah. The results of the study indicate that the considerations taken by judges are based on the aim of maintaining the welfare of children, such as moral protection and long-term welfare in line with maqashid sharia. The uniqueness of this study lies in the application of Imam Al-Syatibi's maqashid theory in analyzing judges' considerations after the enactment of Law No. 16 of 2019 concerning marriage, especially regarding marriage dispensation as a solution to address guardians' concerns about children amidst today's free association. This study recommends strengthening judges' understanding of the maqashid sharia in marriage dispensation to be more consistent in achieving the community's welfare. In addition, policy reform is needed to tighten dispensation granting by considering adolescents' social and moral development. Overall, this study can provide insight to improve the quality of court decisions in cases of marriage dispensation by the maqashid sharia